Post-Infectious Inflammatory Response Syndrome in an HIV-Negative Immunocompetent Elderly Patient With Cryptococcal Meningitis: A Case Report and Literature Review - Liu, Junyu; Liu, Jia; Qin, Bang-e; Yao, Shiqi; Wang, Anni; Yang, Lu; Su, Zhihui; Xu, Xiaofeng; Jiang, Ying; Peng, Fuhua (Frontiers in Immunology, 2022)
We report a previously healthy 82-year-old male with cryptococcal meningitis (CM) who represented neurological deterioration due to post-infectious inflammatory response syndrome (PIIRS) occurring in 4 months after initial antifungal therapy. He was treated with corticosteroids for 2 months and recovered clinically. However, the clinical manifestation, cerebrospinal fluid (CSF), and brain magnetic resonance imaging (MRI) results got worse again on the next day after corticosteroid withdrawal. The analysis of inflammatory cytokines and culture on CSF, as well as brain MRI, still suggested a diagnosis of PIIRS. Therefore, corticosteroid therapy was used again and he subsequently obtained a complete resolution of symptoms.